Cameroon : Poverty Reduction Strategy Paper-Progress Report- Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The fourth annual progress report on the implementation of the Poverty Reduction Strategy (PRS) provides a generally candid review of achievements and obstacles in implementation during 2006. The current report incorporates to a limited extent IMF staff recommendations from the previous Joint Staff Advisory Note (JSAN). The ongoing preparation of an updated PRS provides an opportunity to address more forcefully growth bottlenecks in Cameroon. The report covers a period of good external and fiscal performance, but accompanied by a significant decline in economic growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet